Analisis Yuridis Putusan No. 3/Pdt.G.S/2020/Pn.Sel Tentang Wanprestasi Nasabah PT. Bank Perkreditan Rakyat (BPR) Segara Anak Kencana - Teguh Purnama Aji; Aris Munandar (Fakultas Hukum Universitas Mataram, 2022)
This research has the purpose (1) to find out the judge's legal consideration in the court decision number No. 03/Pdt.G.S/2020/PN.Sel concerning contract default in the PT. Bank Perkreditan Rakyat (BPR) Segara Anak Kencana credit agreement, and (2) to find out the legal consequences against the court decision number 3/Pdt.G.S/2020/PN.Sel concerning contract default in the credit agreement. The research method in this study uses the normative legal research method, which uses the statute approach, the cases approach, and the conceptual approach. The result of this study in this research that the judge's legal consideration is considering the defendant has contract default based on the agreement they made according to Article 1243 Indonesia Civil Code. Furthermore, the legal consequence, in this case, the agreement can be null and void, and the defendants must give compensation, change of risk in the guarantee object based on the substance of the agreement, and paying the court duty fee administration.